HARMONISASI PENDIDIKAN SAINS DAN ISLAM MELAUI PENDEKATAN STEAMER (MEMBANGUN GENERASI KIMIA ABAD 21) - Shorihatul Inayah, S.Pd. (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
Modern education that is currently being introduced is the STEAMER approach (Science, Technology, Engineering, Art, Mathematics, Economy and Religious) as the development of chemical life skills on Redox Reaction material. This learning supports the development of collaborative, creative and innovative skills to solve existing problems in the industrial revolution era 4.0. Therefore, the focus of this research is to develop the Harmonization of Science and Islamic Education through the STEAMER approach. This research was conducted at MAN 1 Tuban in the odd semester of TP 2019/2020. The research subjects were students of class XII Natural Science 2. This study was a qualitative study. Data collection techniques used are observation, interviews, reflective journals, documentation and questionnaires, making simple tool products. The results showed that each STEAMER stage can bring life skills in the era of disruption. Application of the STEAMER approach in learning can develop harmonization, namely critical religious thought and problem solving, creative and innovative, communication and collaboration, information literacy, media literacy, technology literacy, entrepreneurship , flexibility is accompanied by religious attitudes in the 21st century.